A heterogeneidade estrutural da economia sergipana no período 2002-2019 - Santos, Marcos Messias dos (2023)
The present work has as its object of research the productive structure of the state of Sergipe in the period from 2002 to 2019. It works here with the central problem of verifying the occurrence in the economy of this state of the phenomenon of Structural Heterogeneity, in the period considered. The analysis is based on the measurement of labor productivity in the primary, secondary and tertiary sectors, with a particular investigation of the performance of the industrial sector and its contribution to the state's gross added value. The central hypothesis that guided the work was that the macro-sectors showed productivity asymmetries over the period of analysis, with a tendency for this phenomenon to be reproduced over time. In order to achieve the objective of the research, the methodology used was based on: i) a theoretical discussion, which had as its main theoretical-analytical reference the ECLAC’s Theory of Underdevelopment and its postulates of primacy of labor productivity for economic growth, as well as from industrialization to economic development; ii) description of the historical evolution of the productive structure of Sergipe's economy, correlating it to the movements of the national and international economy; iii) analysis of the performance of the industrial sector in Sergipe, from 2002 to 2019, relating it to the industrial policies implemented in the period, as well as to the transformations that occurred in the Brazilian economy; and iv) measurement and analysis of the behavior of labor productivity in the macrosectors of Sergipe's productive structure from 2002 to 2019, seeking to correlate the trends verified with the performance of the sectors. The hypothesis was confirmed that the phenomenon of Structural Heterogeneity was present in Sergipe's productive structure in the period 2002 to 2019, manifesting itself in the disparities in productivity between macrosectors, with a general downward trend of this variable in the main wealth-generating sectors – industrial and services –, in the last phase of the period under analysis, which tends to contribute to the deterioration of the state's socioeconomic conditions. Likewise, the permanence of strong asymmetries in productivity between the urban sectors – industry and services – and the rural sector – agriculture and livestock – indicate that the phenomenon of structural heterogeneity tends to reproduce itself in Sergipe's economy